Unconquerable Nation: Knowing Our Enemy, Strengthening Ourselves - Jenkins, Brian Michael (RAND Corporation, 2023)
The author presents a clear-sighted and sobering analysis of where we are today in the struggle against terrorism. Jenkins, an internationally renowned authority on terrorism, distills the jihadistsÂ• operational code and outlines a pragmatic but principled approach to defeating the terrorist enterprise. We need to build upon our traditions of determination and self-reliance, he argues, and above all, preserve our commitment to American values.